New Investigation on the Generalized K-Fractional Integral Operators - Rashid, Saima; Hammouch, Zakia; Kalsoom, Humaira; Ashraf, Rehana; Chu, Yu Ming (Frontiers in Physics, 2020)
The main concern of this paper is the use of generalized $\mathcal{K}$-fractional integral operator for obtaining the latest generalization of Minkowski's inequality. An interesting feature is the generalization of classical Minkowski's inequality via generalized $\mathcal{K}$-fractional integrals. Additionally, this newly defined integral operator have the competencies to be carried out for the evaluation of numerous numerical issues as uses of the work.